ANALYSIS OF THE CONTENT OF MORAL MESSAGES FOR CHILDREN IN THE FILM JUMBO. - Talenta Dida; Budhi Waskito; Noning Verawati (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study was conducted to analyze the moral messages conveyed to children through the animated film Jumbo, focusing on how moral values are represented through narrative structure, symbols, and visual elements. The research was motivated by the growing role of film as a mass communication medium that not only entertains but also educates and shapes children’s character. Although Jumbo presents themes such as friendship, courage, self-acceptance, empathy, and respect for differences, these values are often delivered implicitly, which may cause audiences, particularly children, to overlook or misinterpret the intended moral messages. Therefore, this research aims to identify the moral messages contained in the film and examine their suitability for child audiences. This study employed a qualitative approach using a descriptive content analysis method. Primary data were obtained through repeated observation of the film to identify significant scenes, dialogues, symbols, and visual representations related to moral values. Secondary data were collected from documentation, including film reviews, articles, and related supporting materials. In addition, informants from the Child Protection Division of DP3A Bandar Lampung City were involved to assess the alignment of the film’s moral messages with child-friendly content standards. The findings indicate that Jumbo contains strong moral messages related to friendship, anti-bullying, emotional resilience, self-acceptance, and spiritual values, which are conveyed through symbolic visuals and character development. The study concludes that Jumbo is suitable as a child-friendly film and has the potential to function as an effective medium for moral education, while also contributing to communication studies, particularly in the analysis of moral messages in audio-visual media.